SANIBEL, FLORIDA. (Public Management (00333611), 2005)
Focuses on the Sanibel Hurricane, recipient of the Public Safety Program Excellence Award in Memory of William H. Hansell, Sr. and Alice Hansell which recognizes a local government and its chief administrator for the most creative public safety program, in Florida. Role of city manager Judith Ann Zimomra; Installation of hurricane shutters; Implementation of a model evacuation, reentry and recovery plan that saved lives, minimized economic losses, and illustrated municipal management at its finest; Revision of hurricane preparedness plan annually to maximize the use of new technology.